Elizabeth I and the Old Testament : biblical analogies and providential rule - Norrie, Aidan (Gender and power in the premodern world., 2023)
Throughout her reign, Elizabeth I and her supporters used biblical analogies to perpetuate the Queen's claim to be England's providential Protestant monarch. While Elizabeth's parallels with various biblical figures--including Deborah, Esther, Judith, David, Solomon, and Daniel--have all received varying levels of attention in the scholarship, this is the first analysis of how biblical analogy functioned as a religio-political tool for Elizabeth across her rei.